Engineering the early bone metastatic niche through human vascularized immuno bone minitissues. (26th April 2021) - Colombo, Maria Vittoria; Bersini, Simone; Arrigoni, Chiara; Gilardi, Mara; Sansoni, Veronica; Ragni, Enrico; Candiani, Gabriele; Lombardi, Giovanni; Moretti, Matteo
Abstract: Bone metastases occur in 65%–80% advanced breast cancer patients. Although significant progresses have been made in understanding the biological mechanisms driving the bone metastatic cascade, traditional 2D in vitro models and animal studies are not effectively reproducing breast cancer cells (CCs) interactions with the bone microenvironment and suffer from species-specific differences, respectively. Moreover, simplified in vitro models cannot realistically estimate drug anti-tumoral properties and side effects, hence leading to pre-clinical testing frequent failures. To solve this issue, a 3D metastatic bone minitissue (MBm) is designed with embedded human osteoblasts, osteoclasts, bone-resident macrophages, endothelial cells and breast CCs. This minitissue recapitulates key features of the bone metastatic niche, including the alteration of macrophage polarization and microvascular architecture, along with the induction of CC micrometastases and osteomimicry. The minitissue reflects breast CC organ-specific metastatization to bone compared to a muscle minitissue. Finally, two FDA approved drugs, doxorubicin and rapamycin, have been tested showing that the dose required to impair CC growth is significantly higher in the MBm compared to a simpler CC monoculture minitissue. The MBm allows the investigation of metastasis key biological features and represents a reliable tool to better predict drug effects on the metastatic bone microenvironment.